2019
DOI: 10.1111/1365-2435.13295
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming and plant biomechanical defences: Silicon addition contributes to herbivore suppression in a pasture grass

Abstract: Plants, notably the Poaceae, often accumulate large amounts of silicon (Si) from the soil. Si has multiple functional roles, particularly for alleviating abiotic and biotic stresses (e.g., defence against herbivores). Recent evidence suggests that environmental change, including temperature changes, can diminish Si accumulation which could affect functions such as herbivore defence. Using a field warming experiment, we grew a pasture grass (Phalaris aquatica) that was either supplemented or untreated with Si (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
1
20
1
Order By: Relevance
“…In the current study we found significant negative effects of Si on herbivory (Figure 4), supporting the strong anti‐herbivory effects of Si found in previous work (Frew et al, 2016; Johnson et al, 2019; Massey & Hartley, 2009). Silicon is generally considered a mechanical defence mechanism, as Si is deposited in the leaves as solid SiO 2 phytoliths, causing abrasion of herbivore mouthparts and general decreased palatability of leaf material (Hartley, Fitt, McLarnon, & Wade, 2015; Massey & Hartley, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the current study we found significant negative effects of Si on herbivory (Figure 4), supporting the strong anti‐herbivory effects of Si found in previous work (Frew et al, 2016; Johnson et al, 2019; Massey & Hartley, 2009). Silicon is generally considered a mechanical defence mechanism, as Si is deposited in the leaves as solid SiO 2 phytoliths, causing abrasion of herbivore mouthparts and general decreased palatability of leaf material (Hartley, Fitt, McLarnon, & Wade, 2015; Massey & Hartley, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…The consistently lower endogenous JA seen in stressed Si‐treated plants (Figure 3A) suggests that some species, when supplemented with Si, may actually be more susceptible to herbivory, particularly if the species relies more on JA‐induced chemical defences rather than Si uptake. In B. distachyon and other grasses, however, the hyper‐accumulation of Si appears to provide a significant defence against herbivory, potentially compensating for any reduction in other JA‐induced defences (Frew et al, 2017; Johnson et al, 2019; Ryalls et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silicon in plants has been found to provide resistance to many adverse biotic and/or abiotic environmental conditions, including, for example, nutrient deficiency, drought and toxic metal stress, pathogen intrusion, antiherbivory and mechanical stress (Cooke & Leishman, ; Coskun et al, ; Frew, Weston, Reynolds, & Gurr, ; Guntzer, Keller, & Meunier, ; Strömberg et al, ). The common view has been that the main function of foliar Si accretions in solid form (e.g., phytoliths) is to protect plant tissues from herbivory (Cooke et al, ; Epstein, ; Hartley & DeGabriel, ; Hartley, Fitt, McLarnon, & Wade, ), especially from being eaten by (mostly mammalian) vertebrates (Massey & Hartley, ; Massey, Massey, Ennos, & Hartley, ; Strömberg et al, ; Teaford, Lucas, Ungar, & Glander, ; Wieczorek, Zub, Szafrańska, Książek, & Konarzewski, ) or invertebrates (Garbuzov, Reidinger, & Hartley, ; Hunt, Dean, Webster, Johnson, & Ennos, ; Johnson et al, ; Massey & Hartley, ; Reynolds, Keeping, & Meyer, ; Ryalls, Hartley, & Johnson, ; Soininen, Bråthen, Jusdado, Reidinger, & Hartley, ), and to act as a potentially cheap alternative to cellulose or lignin (Cooke & Leishman, ; Raven, ; Schoelynck et al, ). Silicon is even thought to have played a central role in the co‐evolution of grasses and their mammalian grazers, which had to evolve teeth that could withstand chronic erosion by foliar phytoliths, although this role is still under active debate (Calandra, Zub, Szafrańska, Zalewski, & Merceron, ; Hartley & DeGabriel, ; Strömberg et al, ).…”
Section: Introductionmentioning
confidence: 99%